New interaction and combined multi-wave solutions for the Heisenberg ferromagnetic spin chain equation - Yusuf, Abdullahi; Tchier, Fairouz; İnç, Mustafa (Springer Heidelberg, 2020)
In the current study, rational, interaction and combined multi-wave solutions are obtained for Heisenberg ferromagnetic spin chain equation by using the logarithmic transformation and symbolic computation with ansatz functions. By the choice of suitable parameter values, the dynamics of these obtained solutions are analyzed and represented in figures. The dynamics and characteristics of lump-kink, soliton and multi-wave interactions observed through graphical analysis.
Keywords: Wave Solutions; Rational Solutions; Soliton; Time